2017
DOI: 10.1073/pnas.1709255114
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in inhibitors of Wnt, BMP, and Ras/ERK signaling pathways in non-syndromic midline craniosynostosis

Abstract: Non-syndromic craniosynostosis (NSC) is a frequent congenital malformation in which one or more cranial sutures fuse prematurely. Mutations causing rare syndromic craniosynostoses in humans and engineered mouse models commonly increase signaling of the Wnt, bone morphogenetic protein (BMP), or Ras/ERK pathways, converging on shared nuclear targets that promote bone formation. In contrast, the genetics of NSC is largely unexplored. More than 95% of NSC is sporadic, suggesting a role for de novo mutations. Exome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(111 citation statements)
references
References 51 publications
5
102
2
2
Order By: Relevance
“…The involvement of FGF (fibroblast growth factor), FGFR (fibroblast growth factor receptor), and MAPK/ERK signaling pathways in CRS has long been discussed in the literature (Marie et al, 2005; Shukla et al, 2007; Kim et al, 2015; Kosty and Vogel, 2015; Pfaff et al, 2016; Timberlake et al, 2017). However, our top hit gene-set is KEGG’s cancer pathway, and this link between CRS and cancer is to our knowledge rarely discussed in the literature.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The involvement of FGF (fibroblast growth factor), FGFR (fibroblast growth factor receptor), and MAPK/ERK signaling pathways in CRS has long been discussed in the literature (Marie et al, 2005; Shukla et al, 2007; Kim et al, 2015; Kosty and Vogel, 2015; Pfaff et al, 2016; Timberlake et al, 2017). However, our top hit gene-set is KEGG’s cancer pathway, and this link between CRS and cancer is to our knowledge rarely discussed in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…These 17 new genes found through this process were added to the CRS genes list: AXIN2 (Yilmaz et al, 2018), BBS9 (Justice et al, 2012; Sewda et al, 2019), BCOR (O’Byrne et al, 2017) (for Oculo-facio-cardio-dental syndrome, or microphthalmia syndrome), BGLAP (Sowińska-Seidler et al, 2018), COLEC10 (for 3MC syndrome) (Munye et al, 2017), FGFRL1 (Rieckmann et al, 2009) (for Antley-Bixler syndrome), GCK (for Greig cephalopolysyndactyly syndrome) (Zung et al, 2011), LMNA (Sowińska-Seidler et al, 2018), PPP3CA (Mizuguchi et al, 2018), PTH2R (Kim et al, 2015), RAF1 (for Noonan syndrome with multiple lentigines, or leopard syndrome) (Rodríguez et al, 2019), SIX2 (for frontonasal dysplasia syndrome) (Hufnagel et al, 2016), SMURF1, SPRY1, SPRY4 (Timberlake et al, 2016, 2017), TCOF1 (for Treacher Collins syndrome) (Horiuchi et al, 2004), TNFRSF11B (for Juvenile Paget disease) (Saki et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of signalling cues is very important for understanding the pathophysiology of craniosynostosis. A recent study, in fact, has identified a number of de novo mutations in negative regulators of the Wnt, BMP and Ras/ERK pathways, occurring in non-syndromic midline craniosynostosis patients 25 . These pathways, knowingly implicated in positive regulation of osteogenesis, are, among other signals previously studied 18 , good candidates for dura mater’s regulatory milieu in the context of suture patency and fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of this SNP in the SMAD6 mutation-positive individuals provides strong evidence of epistatic interaction between SMAD6 and BMP2 . This 2-locus model is estimated to be the genetic cause in approximately 3.5% of all the craniosynostosis cases [Timberlake et al, 2016], and the results have been replicated by Timberlake et al [2017]. Activation of BMP receptors leads to phosphorylation of receptor SMADs, which can complex with SMAD4, translocate to the nucleus, and partner with RUNX2 to induce transcription of genes that promote osteoblast differentiation [Hata et al, 1998;Javed et al, 2008] as summarized by Timberlake et al [2016].…”
Section: Slc25a24mentioning
confidence: 93%